A Radiologist’s Guide to IDH-Wildtype Glioblastoma for Efficient Communication With Clinicians: Part II–Essential Information on Post-Treatment Imaging - Vollmuth, Philipp; Karschnia, Philipp; Sahm, Felix; Park, Yae Won; Ahn, Sung Soo; Jain, Rajan (Korean Journal of Radiology, 2025)
Owing to recent advancements in various postoperative treatment modalities, such as radiation, chemotherapy, antiangiogenic treatment, and immunotherapy, the radiological and clinical assessment of patients with isocitrate dehydrogenase-wildtype glioblastoma using post-treatment imaging has become increasingly challenging. This review highlights the challenges in differentiating treatment-related changes such as pseudoprogression, radiation necrosis, and pseudoresponse from true tumor progression and aims to serve as a guideline for efficient communication with clinicians for optimal management of patients with post-treatment imaging.
CRIS-Team Scopus Importer:2025-02-14
Keywords: Glioblastoma; Magnetic resonance imaging; Pseudoprogression; Pseudoresponse; Radiation necrosis